Factors influencing intention to purchase fraudulent honey among Malaysian consumers - Ahmad, Nur Nisaa; Mohd Sharif, Siti Nurhayati Khairatun; Ungku Zainal Abidin, Ungku Fatimah (Human Resource Management Academic Research Society, 2021)
This paper aims to assess consumer awareness about fraudulent honey and its impact on purchase intention using an extended Theory of Planned Behaviour model. An online questionnaire survey was administered among honey consumers in Malaysia. Multiple regression analysis was employed on the 289-obtained-data to generate the relationship between awareness, attitude, subjective norms, perceived behavioural control, and consumers' intention to purchase fraudulent honey. Findings show that attitude and perceived behavioural control have a significant and positive relationship with the intention to purchase fraudulent honey. Consumers' unfavourable attitude towards fraudulent honey diminishes their intention to purchase it. Whereas, even with high perceived behavioural control, consumers decide to purchase fraudulent honey because it fulfils their needs. Consumers are aware of fraudulent honey and choose to buy it since it is cheaper and readily available. This study's practical implication is for marketers and policymakers to develop programs or create proper channels to educate consumers in making wise purchasing decisions. Ultimately, consumers have the right to make their own decision.